Macadamia integrifolia: A New Source of Natural Dyes for Textile Colouration - Habib, Md. Ahsan; Pervez, Md. Nahid; Mahmud, Sakil; Rasel Khan, Meer Md.; Heng, Quan (Asian Journal of Chemistry, 2017)
In this research, an attempt has been made to extract natural dye from Macadamia integrifolia, as a new source for cotton dyeing with good enough properties for potential commercial applications. Optimum extractions were observed with a sodium hydroxide as solvent at 60 °C, time 60 min and M:L was 1:20. The study of different factors effecting dyeability of cotton fabrics were acquired at following conditions: dye concentration 50 %, salt concentration 10 g/L, pH 8, 85 °C and 120 min. The colour strength (K/S) and fastness properties were found to be satisfactory in the post-mordant-processed fabric with the use of optimum mordant (M1 > M3 > M2) concentration of 3 %. Based on UV-visible spectra analysis, presence of lignin was confirmed on extract of aqueous Macadamia integrifolia. The chemical composition analysis was determined by Fourier transform infrared spectroscopy (FT-IR) and surface morphology of cotton fibers were investigated by scanning electron microscopy (SEM) for any changes on fiber. It is hoped that with analytical assay natural colourants can be tailored to access acrimonious functional ambit of synthetic dyes for the textile industries up to some extent, especially in case of the natural fibers colouration.